2015
DOI: 10.1093/occmed/kqv074
|View full text |Cite
|
Sign up to set email alerts
|

Data warehouse for detection of occupational diseases in OHS data

Abstract: Significant differences in indices of workers' health were observed between sectors. This information is now being used in the implementation of a sector-oriented health surveillance programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…A Spanish study using data from the Surveillance System for Nontransmissible Diseases Risk Factors (SIV-FRENT) for the Madrid region found that drivers accumulated more than two cardiovascular risk factors more often than other occupations (Zimmermann Verdejo et al 2010). An analysis of data from our data warehouse on health complaints, medication, and sickness absence by economic sector between 2010 and 2014 revealed that transport and storage were the top two for cardiovascular health problems and cardiovascular medication (Godderis et al 2015). One reason for these findings could be the sedentary aspect of driving that may attract an older and less active population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A Spanish study using data from the Surveillance System for Nontransmissible Diseases Risk Factors (SIV-FRENT) for the Madrid region found that drivers accumulated more than two cardiovascular risk factors more often than other occupations (Zimmermann Verdejo et al 2010). An analysis of data from our data warehouse on health complaints, medication, and sickness absence by economic sector between 2010 and 2014 revealed that transport and storage were the top two for cardiovascular health problems and cardiovascular medication (Godderis et al 2015). One reason for these findings could be the sedentary aspect of driving that may attract an older and less active population.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, 222 occupational health nurses and 179 occupational physicians from IDEWE performed medical examinations and recorded data in the workers' electronic medical files. The data stored in the electronic medical files were loaded into a data warehouse described by Godderis et al, according to Belgian and international privacy and ethical legislation, allowing post hoc analysis of anonymised data (Godderis et al 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the European Union, 46% of people within the labour market reported to have work limitations due to health problems (Eurostat 2015 ). Within the health care sector, a particular large proportion of over 60% of the employees was found to have health problems (Godderis et al 2015 ). Musculoskeletal diseases (MSD), cardiovascular diseases (CVD), mental disorders (MD), and respiratory diseases (RD) have been identified as important causes of sick leave (Ferrie et al 2009 ; Vahtera et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…OHS are indeed complex to evaluate and present many scientific challenges for researchers: benefits are often preventative and therefore more difficult to observe (or only in the long run), have a multidimensional and interacting nature (eg, better workers’ health has a range of economic knock-on effects, for instance reduced staff turnover), involve several ‘intangible’ benefits (eg, an improved reputation), and large datasets are usually required 12. Moreover, strong study designs that minimise confounding are often difficult to implement in practice.…”
mentioning
confidence: 99%